Portuguese version of the Firefighter Coping Self-Efficacy Scale: Factor structure and psychometric characteristics - Moniz, Soraia (2022)
Background and Aim: The current study aimed to translate the Firefighter Coping Self-Efficacy Scale (FFCSE) and explore its dimensionality and psychometric characteristics. Method: This cross-sectional study was authorised by the National Emergency and Civil Protection Authority and disseminated by firefighters' stations from different districts. A sample of 155 firefighters completed online the following self-report instruments: Firefighter Coping Self-Efficacy Scale, Comprehensive Assessment of Acceptance and Commitment Therapy Processes, World Health Organization Index-5, Perceived Stress Scale and Patients Health Questionnaire-4. An exploratory factor analysis was computed, and reliability and validity studies were conducted. Results: The Portuguese version of the FFCSE items revealed, in general, good psychometric characteristics, except for item 10 ("Having dreams about difficult calls"). The factor structure was one-dimensional. The FFCSE showed good internal consistency, and the associations with the other variables were in the expected direction. No differences were found between men and women in the FFCSE mean scores. There was no statistically significant association between the FFCSE and age, years of education or length of service as firefighters. Conclusions: The FFCSE proved to be a one-dimensional measure of perceived self-efficacy to deal with the demands inherent to the firefighter activity. The results suggest that it is a valid and reliable measure, useful in research, clinical and training contexts for these professionals.